FINITE ELEMENT MODELING AND VIBRATION-DAMPING CHARACTERISTICS OF A CONSTRAINED DAMPING BEAM WITH TRANSITION LAYER - LANG BaoXiang; YAN BiJuan; ZHAO ZhangDa; XU Peng (Jixie qiangdu)
The three-layer constrained damping structure is often used in the design of vibration and noise reduction for engineering structures. A "transition layer" can be added in the middle of the viscoelastic layer and the base layer to form a new kind of constrained damping structure with transition layer in order to increase its anti-vibration performance. Based on the first-order shear deformation theory and Hamilton principle, the finite element model is established, and the corresponding vibration and damping characteristics are analyzed. In order to verify the correctness of the model, the two results are in good agreement compared with the analytical solution. Taking the cantilever damping beam as an example, compared with the traditional constrained damping beam, the calculation results show that adding the "transition layer" can improve the loss factor of the structure and energy consumption. At the same time, the material of the transition layer selection and influence of its parameters on the natural frequency and the loss factor of the system are discussed, which lay a good foundation for further optimization and engineering practice.